The Debate about the Government in New Granada: A Metric Lexical Analysis of the Press (1810-1820) - Penagos Carreño, Julián Enrique (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2016)
The present work is aimed at exposing a part of the research called “Cultural History of the Press in Colombia (1810-1820).” It performed a metric lexical analysis to six newspapers of the time. This paper deals with the reflection that was done around the issue of government in Nueva Granada during the Napoleonic invasions. It is a situation characterized by a power emptiness in the colonies due to the abdication and subsequent arrest of King Ferdinand VII. The discussion staged in newspapers shows the ideological fragmentation of neogranadinos enlightened and struggles of significance in relation to the form of government, loyalty to the king and the legitimacy of independence.